51 UMPSA students will contest in 2023 2024 Campus Election - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
GAMBANG, 15 December 2023 – The process of nominating candidates for the Students’ Representative Council (MPP) of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Session 2023/2024 went well and saw a total of 51 students contesting for 27 seats, namely eight general seats and 19 faculty seats in the 2023/2024 Campus Election Session.